Living labs for health: an integrative literature review. (6th June 2019) - Kim, Junghee; Kim, You Lim; Jang, Hyoeun; Cho, Mikyeong; Lee, Mikyung; Kim, Jonggun; Lee, Hyeonkyeong
Abstract: Background: Living labs are user-focused experimental environments in which users and producers co-create innovative solutions in real-life settings. The aim of this study was to review and synthesize health-related studies that used the living labs approach. Methods: An integrative literature review of 15 studies was conducted on the application of living lab principles and their usefulness for investing health problems. Three reviewers independently used methodological assessment tools to evaluate the data quality. Results: Twelve of 15 studies were published during the past 5 years, while 14 of the 15 studies were conducted in Europe. Older adults were the target population in 9 of the 15 studies. The research topics varied, including detecting and monitoring daily life, fall prevention and social support. All the studies applied multi-method approaches and a real-life setting. Use of the living lab approach appeared to improve the quality of life, physical and social health and cognitive function of the target populations. Conclusions: The results showed that the living lab approach was more commonly used to investigate health problems in older adult populations. Living lab appears to be an appropriate method for developing innovative solutions to improve the health of vulnerable groups.